A narrative assessment of synergic inquiry: Its effectiveness in fostering transformative learning in cross-cultural settings. - Masaji Takano (Adult Education Research Conference, 1997)
This empirical study examines the effectiveness of Synergic Inquiry as a practical methodology for fostering transformative learning experience in cross-cultural settings. The study qualitatively analyzes the life narratives of participants who engaged in action-oriented projects conducted abroad that applied the Synergic Inquiry framework.